2020
DOI: 10.3390/agriculture10020038
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Water Quality Indicators of Diversified Farming Systems in a Saline Region of the Mekong Delta, Vietnam

Abstract: Saltwater intrusion, a consequence of climate change and decreased water levels, has been increasingly severe in the Mekong Delta region. Thanh Phu District, Ben Tre Province, Vietnam, is a coastal region where agricultural production and local livelihood have been impaired by saltwater intrusion, resulting in the adoption of multiple coping strategies, including rotations and intercropping. This study aims to measure and evaluate soil and water quality indicators of multiple farming systems in Thanh Phu distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 17 publications
1
20
1
Order By: Relevance
“…Owing to the dynamic nature of coastal areas, agriculture in the coastal zones is quite vulnerable to the unprecedented impacts of climate change. Nevertheless, coastal agriculture all over the world is also experiencing mounting pressure from non-climatic stressors [3,4], with Sri Lanka being no exception. Jaffna Peninsula, located in the northern coastal province of Sri Lanka, is one of the worst affected regions of the country, where increasing coastal salinization is being blamed for decreasing agricultural productivity and abandonment of previously cultivated lands.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the dynamic nature of coastal areas, agriculture in the coastal zones is quite vulnerable to the unprecedented impacts of climate change. Nevertheless, coastal agriculture all over the world is also experiencing mounting pressure from non-climatic stressors [3,4], with Sri Lanka being no exception. Jaffna Peninsula, located in the northern coastal province of Sri Lanka, is one of the worst affected regions of the country, where increasing coastal salinization is being blamed for decreasing agricultural productivity and abandonment of previously cultivated lands.…”
Section: Introductionmentioning
confidence: 99%
“…The 2015-2016 El Niño Southern Oscillation phenomenon caused the second-most severe drought episode and salinity intrusion since 1965 in Vietnam (CGIAR Research Program on Climate Change, 2016) and negatively impacted nearly 250,000 ha of rice production areas (Ministry of Agriculture and Rural Development, 2016) in the Mekong Delta region. Besides, salinity intrusion does not only affect agricultural production, but it also undermines the freshwater reservoir used for household consumption and irrigation (Tan, Tran, & Loc, 2020). Using climate change and rice yield simulation models for the Mekong Delta, Tan Yen et al (2019) found that the wet-season rice crops are projected to decline by 720,450 t during 2020-2050 under the RCP4.5 scenario and by 1.17 Tg under the RCP8.5 scenario considering years with average salinity intrusion and flooding.…”
Section: Crop Sciencementioning
confidence: 99%
“…Several adaptation strategies have been promoted by the government of Vietnam and adapted by farmers to cope with salinity intrusion including rotation of rice with different shrimp species proven to be popular and economically viable (Loc, Thi Hong Diep, Can, Irvine, & Shimizu, 2017;Nguyen et al, 2019;Thi Nhung, Le Vo, Van Nghi, & Quoc Bang, 2019). However, Tan et al (2020) found that water from shrimp growing ponds in the region has low alkalinity and has excessively high H 2 S, which adversely affected shrimp growth and development, making it an unreliable alternative in the long run unless remediation actions will be done in aquaculture ponds. Another adaptation strategy being promoted by the International Rice Research Institute (IRRI) and the Cuu Long Delta Rice Research Institute, through the Consortium for Unfavorable Rice Environments, is the use of salt-tolerant rice varieties, which can potentially reduce the impacts of salinity intrusion in the farmers' field while keeping the rice yield penalty to a minimum (Paik, Le, Nhu, & Mills, 2020).…”
Section: Crop Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Like many of the large river deltas worldwide, the VMD has been recently threatened by various environmental pressures, such as sea-level rise, land subsidence, floods, droughts, salinity intrusion, river bed incision, coastal erosion, and river bank (RB) erosion [1,2,[4][5][6][7][8]. The ever-increasing environment poses multiple critical impacts on the sustainability of the livelihoods of millions of VMD inhabitants [9][10][11][12]. Among these, RB erosion has not been given enough attention due to its complex phenomenon involving many physical-chemical processes and data shortage.…”
Section: Introductionmentioning
confidence: 99%